2013
DOI: 10.1163/15707563-00002405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bt cotton on the immune system and histology of the midgut of the fall armyworm Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae)

Abstract: Despite the efficiency of transgenic plants expressing Bacillus thuringiensis (Bt) toxins as insecticides against several lepidopterans, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is one species that presents low susceptibility to most Bt crops. This study investigated the effects of the Cry 1 Ac toxin expressed by Bt cotton in the midgul of S. frugiperda and its effects on the humoral and cellular immune responses. Three hypotheses were proposed and tested with contributing factors for the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Moreover, no increase in ISC proliferation was detected after exposure of susceptible larvae to the Bt pesticide, suggesting that S. exigua larvae may not respond to exposure to Cry toxins by activating the gut healing response. In agreement with this observation, feeding of Spodoptera frugiperda larvae on Bt cotton producing the Cry1Ac toxin resulted in epithelial damage, which was not associated with an increase in ISCs when comparing to feeding on non-Bt cotton isoline [68]. Because diverse time points were not examined in those reports, an alternative explanation for these observations of no ISC increase is that the ISC differentiation was predominant over proliferation during the time of observation, as suggested from observations of Alabama argillacea exposed to Bt cotton [69] or exposure to Bt pesticides in susceptible and resistant strains of Plutella xylostella [70].…”
Section: Intestinal Regeneration and Resistance To Btsupporting
confidence: 60%
“…Moreover, no increase in ISC proliferation was detected after exposure of susceptible larvae to the Bt pesticide, suggesting that S. exigua larvae may not respond to exposure to Cry toxins by activating the gut healing response. In agreement with this observation, feeding of Spodoptera frugiperda larvae on Bt cotton producing the Cry1Ac toxin resulted in epithelial damage, which was not associated with an increase in ISCs when comparing to feeding on non-Bt cotton isoline [68]. Because diverse time points were not examined in those reports, an alternative explanation for these observations of no ISC increase is that the ISC differentiation was predominant over proliferation during the time of observation, as suggested from observations of Alabama argillacea exposed to Bt cotton [69] or exposure to Bt pesticides in susceptible and resistant strains of Plutella xylostella [70].…”
Section: Intestinal Regeneration and Resistance To Btsupporting
confidence: 60%
“…Galleriae ( 54 ). Importantly, Cry1A-resistant strains of O. furnacalis ( 31 ), H. armigera ( 55 ) and S. frugiperda ( 56 ) showed higher levels of hemolymph phenoloxidase activity when exposed to Cry1A toxins compared to susceptible insects, suggestive of a potential contribution to the resistant phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of certain bioinsecticides may be correlated to the activation of proPO [ 63 ]. PO levels of Helicoverpa armigera and S. frugiperda were elevated after the larvae were exposed to Cry1Ac toxin [ 32 , 34 ]. In the event of Cry toxicity, the midgut epithelium was gradually breached by the Cry toxins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other different proteins have been reported, such as the ATP-binding cassette (ABC—ABCC2, ABCC3 and ABCA2) transporter [ 25 , 26 , 27 , 28 ], actin, Hsp70 and V-ATPase [ 29 , 30 , 31 ]. In addition to all these membrane proteins, it was reported that immune-related proteins might also contribute to the development of resistance [ 32 , 33 , 34 , 35 , 36 ]. Recently, a study brought evidence of the possible direct binding of the Cry1Ah toxin to phenoloxidase (PO) and other immune-related proteins identified in BBMV samples extracted from susceptible and resistant strains of ACB [ 36 ].…”
Section: Introductionmentioning
confidence: 99%